(untitled) (American Journal of Public Diplomacy and International Studies (2993-2157), 2024)
Today the door to all opportunities for people who are passionate about becoming entrepreneurs in our country is wide open. A favorable business environment is created and the necessary legal guarantees for business entities are established, only knowledge and effective use of these guarantors is the main factor in the development of business. This article explores innovation in entrepreneurship and production, as well as important aspects of the use of modern technologies.